A Review of Methodologies for the Rapid Analysis and Quantification of Gases in Solid Media - Chu Zhang; Leizi Jiao; Yibo Wei; Feng Bao; Rui Guo; Daming Dong (Sensors)
Gas sensors are essential measurement devices that have found extensive applications across various fields, including industry, agriculture, ecological and environmental monitoring, military operations, and biomedical research. Numerous sensing methods based on a diverse range of principles—including optics, electrochemistry, and semiconductors—have been used in the development and manufacture of gas sensing technologies. However, the measurement of certain gases remains challenging when using current sensing techniques and sensors; this is particularly true for the gases that are present in solid media. For example, the nitrous oxide that is emitted from soil is often trapped within soil pores, while a significant portion of the ethylene that is released from fruit dissolves within the flesh of the fruit itself. Measurement of the gases in these situations poses difficulties when using conventional gas sensing methodologies. To enable the detection of these elusive gases, scientists and engineers have devised a variety of specialized approaches over the past two decades. In this review article, we summarize several of these sensing methods—including extraction measurement techniques, in-medium scattering spectroscopy, and the use of micro-nano gas sensing probes—and discuss their respective advantages and disadvantages, along with emerging trends in the development of these techniques.